2013
DOI: 10.1159/000350082
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Cerebrospinal Fluid of Parkinson's Disease Patients Pre- and Post-Deep Brain Stimulation

Abstract: Aims: To investigate alterations in protein expression associated with deep brain stimulation (DBS) in an attempt to elucidate possible mechanisms of action. Methods: Cerebrospinal fluid (CSF), obtained from six Parkinson's disease (PD) patients (pre- and post-DBS) and from six normal healthy controls, was studied for differentially expressed proteins. 2-D DIGE, in combination with MALDI-TOF and TOF-TOF Mass Spectrometry (MS) or ESI-MS, was used to identify the changed proteins (3 PD patients and 3 controls). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 858 publications
(14 citation statements)
references
References 67 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…Changes at the proteomic level have been described in the serum, SN and cerebrospinal fluid of PD patients and in the striatum of toxin-induced parkinsonian rats ( Licker et al, 2014 ; Lu et al, 2014 ; Wang et al, 2013 ; Xiong et al, 2014 ). Therefore, we focused on the toxin-induced changes of protein composition and the possible protective effect of PACAP in the 6-OHDA model.…”
Section: Resultsmentioning
confidence: 99%
“…Changes at the proteomic level have been described in the serum, SN and cerebrospinal fluid of PD patients and in the striatum of toxin-induced parkinsonian rats ( Licker et al, 2014 ; Lu et al, 2014 ; Wang et al, 2013 ; Xiong et al, 2014 ). Therefore, we focused on the toxin-induced changes of protein composition and the possible protective effect of PACAP in the 6-OHDA model.…”
Section: Resultsmentioning
confidence: 99%
“…Treatments with anticoagulants, conditions precluding the safe performance of the lumbar puncture, use of investigational drugs or devices, or significant lab abnormalities were also exclusionary. Those with ablative brain surgery or DBS were excluded based on study findings of altered protein expression in CSF in PD patients post‐DBS implantation …”
Section: Study Design and Rationalementioning
confidence: 99%
“…Those with ablative brain surgery or DBS were excluded based on study findings of altered protein expression in CSF in PD patients post-DBS implantation. 28…”
Section: Pd Exclusion Criteriamentioning
confidence: 99%
“…Proteomics were employed to further our understanding of PD pathological mechanisms. Recent proteomic profiling studies in PD have investigated protein changes in the cerebrospinal fluid, plasma, and brain tissue of PD patients and in the brain tissue of MPTP- and 6-OHDA-treated animal models[ 26 , 27 ]. Proteomic research in PD patients and animal models has shown that overt motor symptoms provide little help in the identification of preclinical biomarkers and preventive therapies for PD.…”
Section: Discussionmentioning
confidence: 99%